2014
DOI: 10.4239/wjd.v5.i4.482
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise training on mitochondrial function in patients with type 2 diabetes

Abstract: Core tip: It is well described that exercise interventions improves insulin sensitivity and maximal oxygen uptake in patients with type 2 diabetes as well as in control subjects. When it comes to adaptations in mitochondrial function after an exercise intervention the literature is more sparse especially in patients with type 2 diabetes. Furthermore the medication that patients with type 2 diabetes are using, are often not described well in the papers, and it is known that the different medication (statins and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 84 publications
1
9
0
1
Order By: Relevance
“…In some studies, both regular moderate intensity exercise [ 45 48 ] and HIIT [ 10 , 49 , 50 ] have shown to improve insulin sensitivity. However, few research has however demonstrated that insulin sensitivity remained unaltered following HIIT [ 33 ] and moderate intensity exercise [ 33 , 35 , 46 ]In addition, there are multiple studies finding improved insulin sensitivity among sedentary non-diabetic subjects [ 24 , 41 , 51 ]An intriguing study demonstrated that 7 consecutive days of exercise at 60–75% of heart frequency reserve improved ISI composite with additional improvement of AUC in a T2D population [ 45 ]. In our study, ISI composite was unchanged in both groups ( Fig 6A ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some studies, both regular moderate intensity exercise [ 45 48 ] and HIIT [ 10 , 49 , 50 ] have shown to improve insulin sensitivity. However, few research has however demonstrated that insulin sensitivity remained unaltered following HIIT [ 33 ] and moderate intensity exercise [ 33 , 35 , 46 ]In addition, there are multiple studies finding improved insulin sensitivity among sedentary non-diabetic subjects [ 24 , 41 , 51 ]An intriguing study demonstrated that 7 consecutive days of exercise at 60–75% of heart frequency reserve improved ISI composite with additional improvement of AUC in a T2D population [ 45 ]. In our study, ISI composite was unchanged in both groups ( Fig 6A ).…”
Section: Discussionmentioning
confidence: 99%
“…T2D is linked to endothelial dysfunction and hypertension [ 46 ]. We have demonstrated significant effects on overall blood pressure following 8 weeks of HIIT ( Table 1 ), which may be of pivotal clinical relevance [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Impaired mitochondrial biogenesis is also a possible cause of apoptosis of skeletal muscle cells in T2DM. 18 The goal of this study was to evaluate the effects of LMHFV on glucose homeogenesis, NAFLD and muscle strength as well as the possible mechanisms on mitochondrial biogenesis and lipid metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial quality control consists of a series of mechanisms, including reactive oxygen species (ROS) scavenging, mitochondrial dynamics, and mitophagy. Studies have revealed that exercise improves mitochondrial quality both in healthy [ 10 ] and in metabolic and neurodegenerative disorders as well as in aging [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%